The pinewood nematode, Bursaphelenchus xylophilus, in Madeira Island - Fonseca, L. (2012)
The environmental conditions in Madeira Island are favorable for the presence and dissemination of the pinewood nematode (PWN), Bursaphelenchus xylophilus. Five hundred Pinus pinaster wood samples were collected in several forest areas and PWN was detected in 22.8 % of the samples. Bursaphelenchus xylophilus isolates from Madeira Island displayed the species-specific diagnostic characters. A morphological variation in the female tail terminus was detected. In most females, the tail presented a broadly rounded terminus and, occasionally, a digitate terminus with a terminal nipple-like extension resembling a mucro. PCR ITS-RFLP analysis revealed that Madeira Island isolates exhibited patterns specific to the species B. xylophilus and similar to virulent isolates. Amplified ITS regions were further sequenced and no genetic diversity was found for this genomic region among 17 Portuguese isolates (Madeira Island and Continental Portugal). Phylogenetic analysis revealed that Portuguese isolates grouped with isolates from China, Korea and one isolate from Japan.